Profiling of rhizosphere-associated microbial communities in North Alabama soils infested with varied levels of reniform nematodes - Karapareddy, Sowndarya; Anche, Varsha C.; Tamatamu, Sowjanya R.; Janga, Madhusudhana R.; Lawrence, Kathy; Nyochembeng, Leopold M.; Todd, Antonette; Walker, Lloyd T.; Sripathi, Venkateswara R. (Frontiers in Plant Science, 2025)
IntroductionPlant roots, nematodes, and soil microorganisms have a complex interaction in the rhizosphere by exchanging or communicating through biomolecules or chemicals or signals. Some rhizospheric (including endophytic) microbes process such compounds via biogeochemical cycles to improve soil fertility, promote plant growth and development, and impart stress tolerance in plants. Some rhizospheric microbes can affect negatively on plant parasitic nematodes (PPNs) thus hindering the ability of nematodes in parasitizing the plant roots. Next-generation sequencing is one of the most widely used and cost-effective ways of determining the composition and diversity of microbiomes in such complex environmental samples.MethodsThis study employed amplicon sequencing (Illumina/NextSeq) of 16S ribosomal RNA (16S rRNA) for bacteria and Internal Transcribed Spacer (ITS2) region for fungi to profile the soil microbiome in the rhizosphere of cotton grown in North Alabama. We isolated DNA (ZymoBIOMICS) from soil samples in triplicates from four representative locations of North Alabama. Based on the level of Reniform Nematode (RN) Infestation, these locations were classified as Group A-RN Not-Detected (ND), Group B-RN Low Infestation (LI), Group C-RN Medium Infestation (MI), and Group D-RN High Infestation (HI) and determined using sieving method and microscopic examination.Results and discussionOur analyses identified 47,893 bacterial and 3,409 fungal Amplicon Sequence Variants (ASVs) across all groups. Among the bacterial ASVs, 12,758, 10,709, 12,153, and 11,360 unique ASVs were determined in Groups A, B, C, and D, respectively. While 663, 887, 480, and 326 unique fungal ASVs were identified in Groups A, B, C, and D, respectively. Also, the five most abundant rhizospheric bacterial genera identified were Gaiella, Conexibacter, Bacillus, Blastococcus, Streptomyces. Moreover, five abundant fungal genera belonging to Fusarium, Aspergillus, Gibberella, Cladosporium, Lactera were identified. The tight clustering of bacterial nodes in Actinobacteria, Acidobacteria, and Proteobacteria shows they are highly similar and often found together. On the other hand, the close association of Ascomycota and Basidiomycota suggesting that they have different ecological roles but occupy similar niches and contribute similar functions within the microbial community. The abundant microbial communities identified in this study had a role in nutrient recycling, soil health, plant resistance to some environmental stress and pests including nematodes, and biogeochemical cycles. Our findings will aid in broadening our understanding of how microbial communities interact with crops and nematodes in the rhizosphere, influencing plant growth and pest management.